2015
DOI: 10.1387/revpsicodidact.13939
|View full text |Cite
|
Sign up to set email alerts
|

Homework and Performance in Mathematics: The Role of the Teacher, the Family and the Student’s Background //Deberes y rendimiento en matemáticas: papel del profesorado, la familia y las características del alumnado

Abstract: The role of teacher, family and the background of students in conducting homework and math performance were investigated. Participants were 7,725 Spanish adolescents with the mean age of 13.78 (± .82) and 2,246 teachers who taught the above mentioned students. A two-level hierarchical linear analysis, students (N = 7,541) and classrooms (N = 353), was performed, adjusted for background and prior achievement variables. The results indicate that the autonomous work of the students is more important than the time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 50 publications
2
8
0
7
Order By: Relevance
“…Analysis demonstrates another two complementary pieces of data which, read together, raise questions about the previous conclusion. In the first place, time spent on homework at the individual level was found to have a negative effect on achievement, which confirms the findings of other multilevel-approach research (Trautwein, 2007; Trautwein et al, 2009b; Chang et al, 2014; Fernández-Alonso et al, 2016). Furthermore, it was found that an increase in assigned homework volume is associated with an increase in the differences in time students need to complete it.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Analysis demonstrates another two complementary pieces of data which, read together, raise questions about the previous conclusion. In the first place, time spent on homework at the individual level was found to have a negative effect on achievement, which confirms the findings of other multilevel-approach research (Trautwein, 2007; Trautwein et al, 2009b; Chang et al, 2014; Fernández-Alonso et al, 2016). Furthermore, it was found that an increase in assigned homework volume is associated with an increase in the differences in time students need to complete it.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, the expectation and motivation variables were included in the group of adjustment factors assuming that in this research they could be considered background variables. In this way, once the background factors are discounted, the homework variables explain 2% of the total variance, which is similar to estimations from other multilevel studies (De Jong et al, 2000; Trautwein, 2007; Dettmers et al, 2009; Fernández-Alonso et al, 2016). On the other hand, the statistical models used to analyze the data are correlational, and as such, one can only speak of an association between variables and not of directionality or causality in the analysis.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, high amount of homework and repetitive exercises are counterproductive to students' achievement (e.g., Fernández-Alonso, Álvarez-Díaz, Suárez-Álvarez, & Muñiz, 2017;Trautwein, 2007;Trautwein, Köller, Schmitz, & Baumert, 2002). Research also indicated that students' autonomous homework completion (second phase) is more beneficial to academic achievement than completing homework with help (Fernández-Alonso et al, 2015;Fernández-Alonso, Suárez-Álvarez, & Muñiz, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite its relevance, parental involvement in children's homework remains as a controversial topic among scholars who have not met a consensus on its effects on academic achievement (Dumont et al, 2012;Hill & Tyson, 2009;Moroni et al 2015). While some scholars (Fernández-Alonso et al, 2016;Xu et al, 2018) report parental involvement in homework as a consistent variable leading students to academic success, others have reported either a weak or a negative association (Barger et al, 2019;Hill & Tyson, 2009;Silinskas et al, 2013;Valle et al, 2015).…”
mentioning
confidence: 99%
“…Specifically, most prior research put special emphasis on analyzing the effects of parental involvement in children's homework in terms of quantity and frequency. Therefore, as suggested by several scholars (Fernández-Alonso et al, 2016;Gonida & Cortina, 2014;Silinskas & Kikas, 2019), further research is needed to also explore the effects of the different types of parental involvement in homework.…”
mentioning
confidence: 99%